Bacteriophage HK022 Nun protein arrests transcription by blocking lateral mobility of RNA polymerase during transcription elongation - Vitiello, Christal L (Landes Bioscience, 2014)
Coliphage HK022 excludes phage λ by subverting the λ antitermination system and arresting transcription on the λ chromosome. The 12 kDa HK022 Nun protein binds to λ nascent transcript through its N-terminal Arginine Rich Motif (ARM), blocking access by λ N and arresting transcription via a C-terminal interaction with RNA polymerase. In a purified in vitro system, we recently demonstrated that Nun arrests transcription by restricting lateral movement of transcription elongation complex (TEC) along the DNA register, thereby freezing the translocation state. We will discuss some of the key experiments that led to this conclusion, as well as present additional results that further support it.